Microbiomes in physiology: insights into 21st‐century global medical challenges. Issue 4 (14th February 2022) - Shehata, Emad; Parker, Aimée; Suzuki, Toru; Swann, Jonathan. R.; Suez, Jotham; Kroon, Paul. A.; Day‐Walsh, Priscilla
Abstract : New Findings: What is the topic of this review? The role of the gut microbiome in physiology and how it can be targeted as an effective strategy against two of the most important global medical challenges of our time, namely, metabolic diseases and antibacterial resistance. What advances does it highlight? The critical roles of the microbiome in regulating host physiology and how microbiome analysis is useful for disease stratification to enable informed clinical decisions and develop interventions such as faecal microbiota transplantation, prebiotics and probiotics. Also, the limitations of microbiome modulation, including the potential for probiotics to enhance antimicrobial resistance gene reservoirs, and that currently a 'healthy microbiome' that can be used as a biobank for transplantation is yet to be defined. Abstract: The human gut microbiome is a key factor in the development of metabolic diseases and antimicrobial resistance, which are among the greatest global medical challenges of the 21st century. A recent symposium aimed to highlight state‐of‐the‐art evidence for the role of the gut microbiome in physiology, from childhood to adulthood, and the impact this has on global disease outcomes, ageing and antimicrobial resistance. Although the gut microbiome is established early in life, over time the microbiome and its components including metabolites can become perturbed due to changes such as dietary habits, use of antibiotics and age. As gut microbial metabolites, including short‐chain fatty acids, secondary bile acids and trimethylamine‐ N ‐oxide, can interact with host receptors including G protein‐coupled receptors and can alter host metabolic fluxes, they can significantly affect physiological homoeostasis leading to metabolic diseases. These metabolites can be used to stratify disease phenotypes such as irritable bowel syndrome and adverse events after heart failure and allow informed decisions on clinical management and treatment. While strategies such as use of probiotics, prebiotics and faecal microbiota transplantation have been proposed as interventions to treat and prevent metabolic diseases and antimicrobial resistance, caution must be exercised, first due to the potential of probiotics to enhance antimicrobial resistance gene reservoirs, and second, a 'healthy gut microbiome' that can be used as a biobank for transplantation is yet to be defined. We highlight that sampling other parts of the gastrointestinal tract may produce more representative data than the faecal microbiome alone.